Short‐chain fatty acids induce tissue plasminogen activator in airway epithelial cells via GPR41&43. Issue 5 (24th March 2018) - Imoto, Y.; Kato, A.; Takabayashi, T.; Sakashita, M.; Norton, J. E.; Suh, L. A.; Carter, R. G.; Weibman, A. R.; Hulse, K. E.; Stevens, W.; Harris, K. E.; Peters, A. T.; et al.
Summary: Background: Chronic rhinosinusitis (CRS) is a heterogeneous chronic inflammatory disease generally divided based on the presence or absence of nasal polyps (NPs). One of the features of NPs is excessive fibrin deposition, which is associated with down‐regulation of tissue plasminogen activator (t‐PA) in NPs. As t‐PA is expressed in epithelial cells, and epithelium is readily accessible to topical therapies, identifying compounds that can mediate the induction of t‐PA would be a potential new strategy for the treatment of NPs. Objective: The objective of this study was to determine whether short‐chain fatty acids (SCFAs) can induce t‐PA in airway epithelial cells via their known receptors GPR41 and GPR43. Methods: We performed immunohistochemistry (IHC) to determine whether receptors for SCFAs, known as G protein‐coupled receptor 41/free fatty acid receptor 3 (GPR41/FFAR3) and GPR43/FFAR2, are expressed in nasal tissue. Primary normal human bronchial epithelial (NHBE) cells were stimulated with different concentrations of SCFAs to test induction of t‐PA, which was analysed by expression of mRNA and protein. Mediation of responses by SCFA receptors was evaluated by specific receptor gene silencing with siRNA. Results: Immunohistochemistry study revealed that airway epithelial cells expressed GPR41 and GPR43. Acetic acid, propionic acid, butyric acid and valeric acid significantly induced t‐PA expression from two‐ to tenfolds. The strongest inducer of t‐PA from NHBE cells was propionic acid; cells stimulated with propionic acid released t‐PA into the supernatant in its active form. Gene silencing of GPR41 and GPR43 revealed that induction of t‐PA by SCFAs was dependent upon both GPR41 and GPR43. Conclusions and Clinical Relevance: Short‐chain fatty acids were shown to induce airway epithelial cell expression of t‐PA via GPR41 and GPR43. Topical delivery of potent compounds that activate these receptors may have value by reducing fibrin deposition and shrinking nasal polyp growth.